Ответ:
Пошаговое объяснение:
х=3 . .............................
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:![2^{x-1}+2^{x}+2^{x+1}=56\\(1+2+2^{2})*2^{x-1}=56\\(1+2+4)*2^{x-1}=56\\7*2^{x-1}=56\\2^{x-1}=8\\2^{x-1}=2^{3} \\x-1=3\\x=3+1\\x=4 2^{x-1}+2^{x}+2^{x+1}=56\\(1+2+2^{2})*2^{x-1}=56\\(1+2+4)*2^{x-1}=56\\7*2^{x-1}=56\\2^{x-1}=8\\2^{x-1}=2^{3} \\x-1=3\\x=3+1\\x=4](https://tex.z-dn.net/?f=2%5E%7Bx-1%7D%2B2%5E%7Bx%7D%2B2%5E%7Bx%2B1%7D%3D56%5C%5C%281%2B2%2B2%5E%7B2%7D%29%2A2%5E%7Bx-1%7D%3D56%5C%5C%281%2B2%2B4%29%2A2%5E%7Bx-1%7D%3D56%5C%5C7%2A2%5E%7Bx-1%7D%3D56%5C%5C2%5E%7Bx-1%7D%3D8%5C%5C2%5E%7Bx-1%7D%3D2%5E%7B3%7D%20%5C%5Cx-1%3D3%5C%5Cx%3D3%2B1%5C%5Cx%3D4)
Пошаговое объяснение:
х=3 . .............................